Upper Structure of Precast Concretes Comparison: PC-I and PC-U in West Outer Ring Road, Surabaya - Jaka Propika; Yanisfa Septiarsilia; Eka Susanti; Heri Istiono (Litbang Pemas - Universitas Islam Lamongan, 2022)
Increasing of motorcycle numbers in big cities in Indonesia, especially in Surabaya. The traffic becomes crowded and road capacity is exceeded. Because of the increasing of motorcycle volume, especially in western part of Surabaya, the government built a flyover in west outer ring road to provide solution to congestion in Surabaya. This study aimed to determine the comparation between PC-I girder and PC-U girder used. In west outer ring road, the method was used to calculate prestressed beam was fully prestressed. The researcher reviewed the prestressed beam from behavior, reaction, and impact to the all of bridge structures from structure. The Software SAP 2000 V.14.2.5 is used to structure calculation analysis. According to analysis result, the calculation has been carried out, the difference ratio of the bridge floor slabs was studied. Flyover model with PC-U prestressed beam had smaller ratio than PC-I. The comparison of strand used in PC-U beams was more than PC-I with 42.22%. The maximum moment value was occurred in PC-I girder beam was 1541.979 Tons.meter and PC-U girder was 2252.599 Tons.meter. The strand requirements and cross area section was comparised too.